“World Health Day and Pediatric Surgery Day 2026: May the Future Generation Be Protected by the Power of Science” (Journal of Paediatric Surgeons of Bangladesh, 2026)
Abstract not availableJournal of Paediatric Surgeons of Bangladesh (2024) Vol. 15 (1 & 2): 1-2